2001
DOI: 10.1067/mtc.2001.116557
|View full text |Cite
|
Sign up to set email alerts
|

Is repair preferable to replacement for ischemic mitral regurgitation?

Abstract: Late survival is poor after surgery for ischemic mitral regurgitation. Most patients with ischemic mitral regurgitation benefit from mitral valve repair. In the most complex, high-risk settings, survivals after repair and replacement are similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
347
2
19

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(379 citation statements)
references
References 26 publications
11
347
2
19
Order By: Relevance
“…35,36 Mitral valve replacement, largely employed in the past in ischaemic regurgitation, although eliminates the short-term risk of recurrent MR, it is associated with poor long-term survival. 37 Thus, in our actual policy, we do not consider MV replacement as a reasonable alternative to repair.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Mitral valve replacement, largely employed in the past in ischaemic regurgitation, although eliminates the short-term risk of recurrent MR, it is associated with poor long-term survival. 37 Thus, in our actual policy, we do not consider MV replacement as a reasonable alternative to repair.…”
Section: Discussionmentioning
confidence: 99%
“…Operative mortality has been reported between 5 and 18% with two-year survival rates of 70% and five-year survival rates of 61%. [13][14][15][16] However, recent studies have shown that valve surgery does not improve survival in patients with left ventricular dysfunction. 17,18 Therefore, different percutaneous techniques were developed, offering an alternative treatment for MR in patients who are poor candidates for surgery.…”
Section: Follow-up Resultsmentioning
confidence: 99%
“…Finalmente, adoptamos el anillo de Carpentier-McCarthy-Adams, especialmente diseñado para la insufi ciencia mitral isquémica ventricular, que incorpora ya una sobre-reducción del diámetro ántero-posterior y una tracción hacia el plano auricular de la porción póstero-medial del anillo mitral, que es la que experimenta mayor tracción hacia apical en el infarto inferior, principal causa de una insufi ciencia mitral isquémica ventricular 28 . Si bien no fue un objetivo de este trabajo precisar cuando la revascularización miocárdica exclusiva o el reemplazo mitral serían el procedimiento de elección, pero sí es motivo de mucha discusión en la literatura 15,[29][30][31] , es conveniente precisar que en nuestra práctica actual cuando la insufi ciencia mitral es poco signifi cativa ( 2+) y el miocardio se presume viable, en general consideramos que la revascularización miocárdica exclusiva es sufi ciente para tratar la insufi ciencia mitral isquémica. En el otro extremo, en insuficiencias mitrales severas (4+), con gran disfunción ventricular, y en pacientes especialmente graves, consideramos el reemplazo mitral de elección, ya que el benefi cio de conservar la integridad de la válvula mitral se anula por el daño ventricular izquierdo intrínseco y la gravedad de los pacientes no hace conveniente aplicar un procedimiento que puede fallar y requerir de un segundo período de circulación extracorpórea.…”
Section: Discussionunclassified